The visual object of desire in late medieval England - Stanbury, Sarah (Philadelphia, Pa. Univ. of Pennsylvania Press, 2008)
Introduction: Premodern fetishes -- Fetish, idol, icon. Knighton's Lollards, Capgrave's Katherine, and Walter Hilton's "Merk ymage" -- The despenser retable and 1381 -- Chaucer's sacramental poetic. Chaucer and images -- Translating Griselda -- The Clergeon's tongue -- Moving pictures. Nicholas Love's Mirror: dead images and the life of Christ -- Arts of self-patronage in The book of Margaret Kempe
Introduction: Premodern fetishes -- Fetish, idol, icon. Knighton's Lollards, Capgrave's Katherine, and Walter Hilton's "Merk ymage" -- The despenser retable and 1381 -- Chaucer's sacramental poetic. Chaucer and images -- Translating Griselda -- The Clergeon's tongue -- Moving pictures. Nicholas Love's Mirror: dead images and the life of Christ -- Arts of self-patronage in The book of Margaret Kempe
Includes bibliographical references (S. [259] - 278) and index
Archivierung prüfen
Archivierung/Langzeitarchivierung gewährleistet
Archivierung prüfen
Keywords: English literature -- Middle English, 1100-1500 -- History and criticism; Iconoclasm in literature; Idols and images in literature; Christian art and symbolism in literature; Iconoclasm -- England -- History -- To 1500; Christian art and symbolism -- England -- Medieval, 500-1500; Art and literature -- England -- History -- To 1500; Civilization, Medieval, in literature